¿Cómo ha cambiado el rol de psicología jurídica en Colombia? - Castellanos Bohorquez, Andrea Carolina; Prada Monroy, Andrés Felipe; Anaya Cárcamo, Graciela María; Roa Leyton, Jeraldine Yulied; Calderón Rojas, Yeimin Adriana; Pastor Palacio, Daniela; Valencia Guaca, Alison Juliana; González Castro, Hellen Lorena; Medina Patiño, Thalía (Universidad Antonio Nariño, 2024)
No aplica